The Student's Error in Forming Nominal Clause in Complex Sentence - Siska Bochari; Hasan Basri; Muh Arid (Institut Agama Islam Negeri Palopo, 2019)
This research uses descriptive qualitative method that aims at analyzing the errors in the formation of nominal clause in complex sentence conducted by students of the fourth semester of the English Language Study Program, Tadulako University. Data collection was taken through giving tests to 49 students. The test was given in the form of a written test by asking students to make nominal clause. The results showed that the most dominant type of error made by students in making nominal clauses is omission, which is to reduce parts of words such as suffix -s as plural marker on nouns or as present marker on verbs. In connection with the functions of nominal clause in sentence, the students have difficulty in making nominal clause that functions as complement and object of preposition.